1996
DOI: 10.1016/s0969-2126(96)00138-4
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of a class II fructose-1,6-bisphosphate aldolase shows a novel binuclear metal-binding active site embedded in a familiar fold

Abstract: Background: Aldolases catalyze a variety of condensation and cleavage reactions, with exquisite control on the stereochemistry. These enzymes, therefore, are attractive catalysts for synthetic chemistry. There are two classes of aldolase: class I aldolases utilize Schiff base formation with an active-site lysine whilst class II enzymes require a divalent metal ion, in particular zinc. Fructose-1,6-bisphosphate aldolase (FBP-aldolase) is used in gluconeogenesis and glycolysis; the enzyme controls the condensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
112
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 47 publications
7
112
0
Order By: Relevance
“…A nonenzymatic glycolysis is accelerated by transition metals (5), and Zn(II) ions are involved in the catalytic mechanism of class I aldolases (21,22). Therefore, we screened for the effects of different metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…A nonenzymatic glycolysis is accelerated by transition metals (5), and Zn(II) ions are involved in the catalytic mechanism of class I aldolases (21,22). Therefore, we screened for the effects of different metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…5). Each subunit (denoted A and B) folds into an (␣/␤) 8 barrel as seen in structures of other bacterial class II aldolases (15,16,20,37).…”
Section: Resultsmentioning
confidence: 99%
“…TBP is specifically targeted for cleavage by the E. coli D-tagatose-1,6-bisphosphate aldolase (ecTBPA), another class II aldolase. The crystal structures of ecFBPA (15,16) and ecTBPA (20) are similar, yet the mechanism for substrate (i.e. stereoisomer) discrimination is not apparent from a comparison of the respective active sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The three latter enzymes display an (␣͞␤) 8 fold, whereas fuculose-1-phosphate aldolase does not. On this basis, it has been suggested that the class II aldolases fall into two distinct categories (37). On the basis of sequence identity and metal-binding preferences, class II aldolases exhibiting an (␣͞␤) 8 fold can be further subdivided into (i) fructose-1,6-bisphosphate and tagatose-1,6-bisphosphate aldolases, which share 23% sequence identity and bind Zn 2ϩ , and (ii) 2-dehydro-3-deoxygalactarate aldolase, unrelated in sequence to either of the above enzymes and preferentially binding Mg 2ϩ .…”
Section: Resultsmentioning
confidence: 99%